2021
DOI: 10.1007/s12403-021-00396-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defined Mixtures of Persistent Organic Pollutants (POPs) on Pre-lethal Cytotoxicity in the Human A-498 Kidney Cell Line In Vitro

Abstract: A total mixture of 29 persistent organic pollutants (POPs) modelled from Scandinavian blood concentrations was used to expose human A-498 kidney cells for 24 h over a concentration range spanning below to above blood level (1/10x, 1x, 50x, 100x, 500x). Its constituent submixtures (PFAA, Br, Cl) and co-mixtures (PFAA + Br, PFAA + Cl, Br + Cl) were also tested. Valinomycin (12 µM) was used as a cytotoxic comparative compound. Cell number (CN), nuclear area (NA), nuclear intensity (NI), mitochondrial membrane pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Using cell reporter assays, this mixture was found to antagonize the androgen receptor transactivation and nuclear translocation [13], to inhibit the transactivation activity of the aryl hydrocarbon receptor [14], and to induce cytotoxicity while it enhances nerve-growth-factor-induced neurite outgrowth in PC12 cells at high concentrations [15]. Microscopic high content analysis (HCA) revealed that some sub-mixtures affected cell number, nuclear area, and mitochondrial membrane potential in A-498 human kidney cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using cell reporter assays, this mixture was found to antagonize the androgen receptor transactivation and nuclear translocation [13], to inhibit the transactivation activity of the aryl hydrocarbon receptor [14], and to induce cytotoxicity while it enhances nerve-growth-factor-induced neurite outgrowth in PC12 cells at high concentrations [15]. Microscopic high content analysis (HCA) revealed that some sub-mixtures affected cell number, nuclear area, and mitochondrial membrane potential in A-498 human kidney cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several sub-mixtures were designed, containing either chlorinated (Cl), brominated (Br), or perfluorinated compounds (PFAA) to be able to assign specific effects to one of these classes [17]. The total POP mixture was shown to antagonize the androgen receptor transactivation and nuclear translocation [18], inhibit the transactivation activity of the aryl hydrocarbon receptor [19], and to enhance the nervegrowth-factor-induced neurite outgrowth in PC12 cells at high concentration [18][19][20][21]. It also induces cytotoxicity and some of the sub-mixtures affect the number of cells, nuclear area and mitochondrial membrane potential in human A-498 kidney cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The total POP mixture was shown to antagonize the androgen receptor transactivation and nuclear translocation [18], inhibit the transactivation activity of the aryl hydrocarbon receptor [19], and to enhance the nervegrowth-factor-induced neurite outgrowth in PC12 cells at high concentration [18][19][20][21]. It also induces cytotoxicity and some of the sub-mixtures affect the number of cells, nuclear area and mitochondrial membrane potential in human A-498 kidney cells [21]. Recently, zebrafish larvae exposed to this POP mix at realistic concentrations, or sub-mixtures thereof, presented growth retardation, edemas, retarded swim bladder inflation, and hyperactive swimming behavior [22].…”
Section: Introductionmentioning
confidence: 99%
“…A compromise characterized by pragmatic and operational efficiency entails targeted assessments of specific chemicals that closely emulate human samples. , A prominent example is the design of a mixture of 29 persistent organic pollutants, whose design was derived from estimated human daily intakes . This mixture has been tested in diverse cellular bioassay, and strong mixture effects were observed; however, due to a lack of single chemical data, consistency with mixture models could not be checked.…”
Section: Introductionmentioning
confidence: 99%